ANTIOXIDANT ACTIVITY OF COMBINATION OF WHITE-PURPLE Orthosiphon aristatus (Blume) Miq HERB EXTRACT AND Stevia rebaudiana Bertoni USING FRAP METHOD - Faramayuda, Fahrauk; Syam, Akhirul Kahfi; Putri, Dhiffa Namira Alifia; Ismail, Nursafira Khairunnisa; Akbar, Tzazkia Febriyana; Farhan (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Oxidative stress is caused by an increase or decrease in the antioxidant defense activity. Orthosiphon aristatus (Blume) Miq and Stevia are two plants that contain antioxidant compounds and can bind free radical compounds. The combination of Orthosiphon aristatus (Blume) Miq and Stevia was expected to increase antioxidant activity. This study aimed to determine the antioxidant activity of a combination of the Orthosiphon aristatus (Blume) Miq white-purple variety and Stevia rebaudiana Bertoni extract. Antioxidant activity was tested using the FRAP method with a UV-visible spectrophotometer at a wavelength of 710 nm. The results of phytochemical screening showed that both plant extracts and dry material contained secondary metabolite compounds, including flavonoids, polyphenols, saponins, quinones, steroid-triterpenoids, and monoterpenes-sesquiterpenes. A qualitative test relating to antioxidants using TLC showed positive antioxidant activity, which was proven by the presence of green or blue light on the TLC plates. This was due to electron transfer in the compound, which reduced Fe3+ to Fe2+. On the other hand, quantitative measurements using the FRAP method showed the antioxidant capacity values consecutively, F1 combination extract (1:1) of 43.725 mg of QE/g extract, F2 combination extract (2:1) of 57.963 mg of QE/g extract, and combination extract of F3 (3:1) of 64.849 mg of QE/g extract. The extract combination of F3 showed the best formula, with a value of 64.849 mg QE/g extract. Keywords: Orthosiphon aristatus (Blume) Miq, Stevia, antioxidants, FRAP